Ultradian oscillation in expression of four melatonin receptor subtype genes in the pineal gland of the grass puffer, a semilunar-synchronized spawner, under constant darkness - Ikegami, Taro; Maruyama, Yusuke; Doi, Hiroyuki; Hattori, Atsuhiko; Ando, Hironori (Frontiers in Neuroscience, 2015)
Melatonin receptor gene expression as well as melatonin synthesis and secretion activities were examined in the pineal gland of the grass puffer, which exhibits unique lunar/tidal cycle-synchronized mass spawing: spawning occurs before high tide on the day of spring tide during spawing season. Melatonin synthesizing activity was assessed by the abundance of arylalkylamine N-acetyltransferase 2 (AANAT2) mRNA. The amount of aanat2 mRNA was low during light phase and initiated to increase after the light was turned off. The secretion of melatonin from primary pineal organ culture was stimulated after the light was turned off and ceased immediately after the light was turned on. The expression levels of four melatonin receptor subtype genes (mel1a1.4, mel1a1.7, mel1b, and mel1c) showed synchronous variations, and the levels tended to be high during the dark phase under light/dark conditions. These results suggest that the action of melatonin on the pineal gland is highly dependent on light and photoperiod, possibly with stronger action during night time. Under constant darkness, the expression of four melatonin receptor subtype genes showed unique ultradian oscillations with the period of 14.0-15.4 h, suggesting the presence of a circatidal oscillator in the pineal gland. The present results indicate that melatonin may serve local chronobiological functions in the pineal gland. These cyclic expressions of melatonin receptor genes in the pineal gland may be important in the control of the lunar/tidal cycle-synchronized mass spawning in the grass puffer.